Paradigma Fiqh Multikultural - Supena, Ilyas (TAJDID, 2019)
The doctrine of the Qur’an teaches that human beings are created in diversities and tribes in order to know one another. Essencially, it means that the basic attitude of Islam exclaims all the humans have the same ideas for a unity of humanity without discriminating races, colour, ethnic, culture and religion. Nevertheless, when the idea of the Qur’an is interpreted in the form of fiqh, historically the fiqh was often confronted with the truth claims being supported by the followers of each madzhab. So, between the truth claims of a fiqh formula being local particular and the doctrine of the Qur’an itself being universal substantial is a paradox. The emergence of the truth claims can have the potential to lead to the conflicts and anarchy among the followers because of differing interpreting of the fiqh. Therefore, a formula of jurisprudence needs to be developed according to multiculturalism that recognizes the diversities and places them in the equality. In the field of jurisprudence, the view of multiculturalism should be methodically built by way of developing paradigm of Islamic social interpretation prioritizing the dynamic, progressive and tolerant interpretations. The discussion in this article concludes that multiculturalist fiqh must be built on the principle of mashlahah using the maqashid al-shari'ah approach. Consequently, universal Qur'anic values are seen as substantive values rather than local-particular values. Therefore, with the maqashid al-shari'ah approach, the values of justice, benefit, equality, wisdom and love are the most important values that will be the source and inspiration when the Qur'an explains the provisions of a legal-specific case.